2019
DOI: 10.3390/biom10010048
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Extracellular Vesicles as Nanotherapeutics for Regenerative Medicine

Abstract: Long thought of to be vesicles that primarily recycled waste biomolecules from cells, extracellular vesicles (EVs) have now emerged as a new class of nanotherapeutics for regenerative medicine. Recent studies have proven their potential as mediators of cell proliferation, immunomodulation, extracellular matrix organization and angiogenesis, and are currently being used as treatments for a variety of diseases and injuries. They are now being used in combination with a variety of more traditional biomaterials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 120 publications
(165 reference statements)
0
69
0
Order By: Relevance
“…As the classical crosslinking is not enough in terms of specificity and efficiency, the most used covalent method nowadays is the Click Chemistry approach, also known as azide alkyne cycloaddition [ 103 ]. With this process, an alkyne moiety reacts with an azide group to form a stable triazole linkage [ 103 ].…”
Section: Engineered Evsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the classical crosslinking is not enough in terms of specificity and efficiency, the most used covalent method nowadays is the Click Chemistry approach, also known as azide alkyne cycloaddition [ 103 ]. With this process, an alkyne moiety reacts with an azide group to form a stable triazole linkage [ 103 ].…”
Section: Engineered Evsmentioning
confidence: 99%
“…As the classical crosslinking is not enough in terms of specificity and efficiency, the most used covalent method nowadays is the Click Chemistry approach, also known as azide alkyne cycloaddition [ 103 ]. With this process, an alkyne moiety reacts with an azide group to form a stable triazole linkage [ 103 ]. Some studies also used a copper catalyst to accelerate the reaction [ 104 ], but several authors demonstrated that a successful binding can be obtained also without the copper catalyst [ 105 ].…”
Section: Engineered Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of methods and technologies have been optimized in EV engineering [ 47 ]. Several strategies to load therapeutics inside EVs and functionalize them to cell targeting have been developed.…”
Section: Extracellular Vesicles (Evs) As a Delivery System For Nucmentioning
confidence: 99%
“…Additionally, GFs have been also used as crosslinkers, contributing to both hydrogel bioactivity and mechanical properties whilst increasing biocompatibility. As we are focusing here on GFs, we will mention briefly other biomolecules, including carbohydrates, due to their high compatibility and low rejection rates, while for larger classes of molecules, including aptamers, lipids and steroidal hormones, we propose the reader excellent reviews in the field [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%